The Influence of Processing Parameters on the Al-Mn Enriched Nano-Precipitates Formation in a Novel Al-Mn-Cr-Zr Alloy Tailored for Power Bed Fusion-Laser Beam Process - Alessandra Martucci; Bharat Mehta; Mariangela Lombardi; Lars Nyborg (Metals, 2022)
Among the recently developed compositions tailored for the power bed fusion-laser beam process (PBF-LB), the novel Al-Mn-Cr-Zr alloy stands out. This composition exploits high solid solution strengthening, achieving a high hardness value in the as-built condition. The produced samples are inherently crack-free and have a good level of densification (~99.5%). The goal of this study is to investigate how this quaternary system is affected by the laser power while retaining a similar volumetric energy density. A comparison between the microstructural features and the mechanical performance was performed on a set of samples processed with power values ranging from 100 to 170 W. Microstructural features were investigated through optical microscopy, Electron Back Scattered Diffraction (EBSD) investigation and feature analysis using advanced microscopy to examine the amount, distribution, and shape of precipitates in the different process conditions. Although the quantitative feature analysis permitted analysis of more than 60 k precipitates for each power condition, all samples demonstrated a low level of precipitation (below 0.3%) with nanometric size (around 75 nm). The mechanical performances of this quaternary system as a function of the laser power value were evaluated with a microhardness test, recording very similar values for the different process conditions with a mean value of approximately 104 HV. The results suggested a very stable system over the tested range of process parameters. In addition, considering the low level of precipitation of nanometric phases enriched in Al-Mn, a supersaturated state could be established in each process condition.